China’s quest for natural resources in Latin America - Felipe Freitas da Rocha; Ricardo Bielschowsky (CEPAL Review, 2018)
This article describes and analyses China’s pursuit of natural resources in Latin America, particularly oil, iron, copper and soybeans, which account for over 70% of its imports from the region. This is motivated by the rapid growth and relative scarcity of natural resources in China itself, and the country’s long-term planning that sees the region as a major supplier. In the case of oil, access occurs mainly through loans for oil and direct investments, while in iron and copper it is obtained through direct investments and imports. The method chosen by China to guarantee supply security seems to involve physical control of the resource in question. In the case of soybeans, the path chosen has involved imports increasingly intermediated by trading companies already present in the region, which have recently been taken over by China.